1995
DOI: 10.1159/000098679
|View full text |Cite
|
Sign up to set email alerts
|

The Duke Experience with Nucleus Caudalis DREZ Coagulation

Abstract: The results of 46 nucleus caudalis DREZ coagulations performed at Duke in the preceding 5 years are reviewed retrospectively, with a mean follow-up of 32 months. Fifteen (38%) of 39 patients with complete data indicated that they would undergo the procedure again. Fifteen (38%) described improved quality of life. Outcome was fair or better in 18 (46%). Complications in the form of ataxia were present in 21 (54%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Neurosurgical procedures like nucleus caudalis DREZ lesioning should be considered as valuable options when the classic treatments fail to reduce pain. There are reports in the literature of response to nucleus caudalis DREZ lesioning in the treatment of anesthesia dolorosa, postherpetic neuralgia, cerebral infarction, PIFP, multiple sclerosis, pain secondary to head trauma, craniofacial surgery, and neoplasm (3)(4)(5)14,25,26,28,29). Gorecki et al (14) reported limited response to the operation among PIFP patients and a small number of patients that maintained their pain-free status in the long-term.…”
Section: █ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurosurgical procedures like nucleus caudalis DREZ lesioning should be considered as valuable options when the classic treatments fail to reduce pain. There are reports in the literature of response to nucleus caudalis DREZ lesioning in the treatment of anesthesia dolorosa, postherpetic neuralgia, cerebral infarction, PIFP, multiple sclerosis, pain secondary to head trauma, craniofacial surgery, and neoplasm (3)(4)(5)14,25,26,28,29). Gorecki et al (14) reported limited response to the operation among PIFP patients and a small number of patients that maintained their pain-free status in the long-term.…”
Section: █ Discussionmentioning
confidence: 99%
“…Gorecki et al (14) reported limited response to the operation among PIFP patients and a small number of patients that maintained their pain-free status in the long-term. Nashold et al reported that less than one-fourth of patients remained pain-free one year after the operation (14,27). Sindou et al concluded that paroxysmal shooting pain was significantly more responsive to the procedure than pain described as a continuous burning sensation (41,42).…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the nucleus caudalis, medial regions of the face are represented rostrally while peripheral regions are represented caudally in a conformation known as the 'onionpeel' pattern. There is also a specific alignment of fibers from the three divisions of the trigeminal throughout its course [20] . The close proximity of these three structures to the nucleus caudalis poses significant risk during surgical procedures involving the nucleus ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…We considered this involuntary movement to be the so-called 'hyperkinésies volitionelles' [9,10] Taira/Kawamura/Takakura an arm dysfunction is documented as a complication of this operation [11]. Because stereotactic thalamotomy is known to relieve such hyperkinetic involuntary movement [10] and the patient also suffered intractable deafferentation pain, we decided to try stimulation therapy from an occipital burr hole.…”
Section: Discussionmentioning
confidence: 99%